Digitalism and Development of Arab Media in the 21st Century - Mousa, Issam (Jordan Journal of Social Sciences, 2019)
Modern Arab media, since its inception as of the early 19th century, has been controlled by authorities, whether foreign and later local, adhering to a governmental one point of view. The four stages of Arab media development (control, defiance, containment, flooding) are analyzed in relation to the critical historical communication theory, which sees that communication impacts the development of societies towards liberalism. In this manner, a fifth stage, a move towards quasi-liberalism, brought about by modern digital communication technology as of the 1990s, has succeeded in breaking existing monopolies of the one view media, and in bringing about noticeable changes in the predominant Arab communication system. New attitudes and values began to form. This created a dilemma to the authoritarian Arab governments, which came with counter measures. But digitalism helped in bringing around the Arab spring.